The influence of integrated marketing communication on the cultural tourism product selection intentions among youth in Ho Chi Minh City, Vietnam - Thai, Truong Dinh; Sinh, Bui Duc (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the impact of integrated marketing communications with the following factors: Advertising, Public Relations, Promotion, Direct Marketing, Electronic Word of Mouth, social media, and Digital Marketing, affecting the intention to visit cultural tourism among young people in Ho Chi Minh City, Vietnam. Sample survey results with 330 participants in the research area, SPSS 25.0, and SmartPLS 4.1.0.0 software were used to analyze data and test research hypotheses using the PLS-Structural Equation Modeling model. The research results show that there are six factors affecting the intention to choose cultural tourism among young people: Public Relations, Sales Promotion, Direct Marketing, Electronic Word of Mouth, social media, and Digital Marketing. The Advertising factor is not significant in this study. Based on the research results, some implications are proposed for managers of cultural tourism destinations and tourism businesses to develop appropriate marketing strategies to attract tourists in general and young people in particular to choose cultural tourism, contributing to the development of the tourism industry and the effective exploitation and conservation of cultural resources.